2018
DOI: 10.17216/limnofish.415933
|View full text |Cite
|
Sign up to set email alerts
|

Sıddıklı Barajı’nda Yaşayan Yayın Balığı (Silurus glanis, L., 1758)’nın Üreme Özellikleri

Abstract: In this study, some reproduction properties (sex ratio, reproduction period, egg diameter and fecundity) of Silurus glanis inhabiting Sıddıklı Reservoir were investigated. A total of 200 samples were caught between September 2015 and August 2016 from different regions of Sıddıklı Reservoir. Sex ratio was calculated as 0.88:1.00 (Female: Male). The sex ratio was not statistically different from the expected 1.00:1.00 (χ2= 0.841, P>0.05). The values of gonadosomatic index (GSI) varied from 0.033 to 11.80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
7
1
0
Order By: Relevance
“…Finally, our findings highlight the importance of comprehensive size-at-maturity data, even in the absence of histological information. This observation aligns with previous studies (Alp et al, 2004; Yazici et al, 2018) and provides valuable insights into catfish biology. However, future research may consider incorporating histological data to further enhance our understanding of European catfish reproductive biology.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Finally, our findings highlight the importance of comprehensive size-at-maturity data, even in the absence of histological information. This observation aligns with previous studies (Alp et al, 2004; Yazici et al, 2018) and provides valuable insights into catfish biology. However, future research may consider incorporating histological data to further enhance our understanding of European catfish reproductive biology.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our analysis revealed a significant positive relationship between oocyte size and both fish length and months, indicating that larger females tend to produce larger oocytes. This observed pattern in oocyte size aligns with findings from populations of European catfish in Eastern Europe (Wisniewolski, 1988;Brujenko, 1967;Bugaj, 1966;Šichšabekov, 1978;Mukhamediyeva & Sal'nikov, 1980) and the Eastern region of Turkey (Alp et al, 2004;Akyurt, 1988;Yazici et al, 2018) (Table 1). Moreover, the size frequency distributions of oocytes revealed that females retained the ability to spawn due to the asynchronous development of oocytes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…There were several researches on the age (Yılmaz et al 2007;Saylar, 2009;Alp et al, 2011;Saylar, 2014), growth (Carol et al, 2009Copp et al, 2009;Uysal et al, 2009;Alp et al, 2011), reproduction (Yazıcı et al, 2018), morphological characters (Ünlü et al, 2012), and the diet (Czarnecki et al, 2003;Bora & Gul, 2004;Alp, 2017) of Wels catfish. However, no studies were conducted on the morphometric biometry of this species.…”
Section: Discussionmentioning
confidence: 99%